EGFR overexpression in canine primary lung cancer: pathogenetic implications and impact on survival. (20th September 2012) - Sabattini, S.; Mancini, F. R.; Marconato, L.; Bacci, B.; Rossi, F.; Vignoli, M.; Bettini, G.
Abstract This study reports the main clinicopathological features of primary lung cancer (PLC) in 37 dogs, with special regard to the pathogenetic and prognostic role of epidermal growth factor receptor (EGFR) overexpression. For each case the following characteristics were evaluated: tumour‐node‐metastasis (TNM) stage, tumour histotype, histological grade, mitotic activity and immunohistochemical expression of EGFR. In samples with available normal lung tissue, the amount of background anthracosis was also measured by image analysis. In 27 tumours (73%) a variable number of cells (20–100%) stained positively for EGFR. The proportion of EGFR‐positive tumours was significantly higher in cases with background anthracosis, and the amount of anthracosis was correlated with the percentage of positive tumour cells. Additionally, a trend towards shortened survival for the high EGFR group was observed. These findings suggest an involvement of EGFR signalling pathway in canine PLC, a negative prognostic significance of protein overexpression and its potential implication in air pollution carcinogenesis.